Anurans as Intermediate and Paratenic Hosts of Helminth Infections in the Rainforest and Derived Savanna Biotopes of Southern Nigeria - Imasuen, Abigail A.; Ozemoka, Habibat J.; Aisien, Martins S. O. (International Journal of Zoology, 2012)
Anurans from the rainforest (Okomu National Park) and derived savanna (Agbede) locations in Nigeria were investigated for their role either as intermediate or paratenic hosts of helminth infections. A total of 269 anuran specimens (157 from the Okomu National Park and 112 from Agbede) were examined. Metacercariae of a strigeoid trematode, two nematode species, a proteocephalid cestode, and an acanthocephalan were recovered from infected hosts. Except for the strigeoid trematode, which was only recorded in the rainforest, there was no ecological dichotomy in the distribution of the larval parasites recorded. Tree frogs from the rainforest only served as second intermediate hosts for the strigeoid trematode. The two nematode larvae (type I and type II) found in the body cavity of the infected host are believed to use them as paratenic hosts. Tree frogs were the predominant intermediate hosts of the proteocephalid cestode larvae in the rainforest, while Ptychadena and Phrynobatrachus spp. served this function in the derived savanna. The occurrence of cystacanths in the anurans from both biotopes confirms their known role as paratenic host for acanthocephalans. Afrixalus dorsalis is a new host record for the ascaridoid nematode while the finding of the strigeoid trematode, the proteocephalid cestode larvae and acanthocephalan cystacanths in the anurans investigated represents new geographical records.